Post Traumatic Growth and Meaning Making in Prolonged Grief through Positive Psychology Interventions: A Pilot Study - Saachi Arora; Dr. Sangeeta Bhatia; Dr. Vibha Sharma (Epistemik Press, 2026)
This study examines the effects of positive psychology interventions on meaning-making processes and post-loss growth among thirty-six individuals who have experienced prolonged grief for a minimum duration of six months. Participants were divided into three groups, namely an individual intervention group, a group-based intervention, and a no-intervention control group. Data were collected through structured interview schedules and analyzed using a qualitative thematic analysis approach. The intervention consisted of a ten-session positive psychotherapy program. The findings revealed a notable decrease in grief intensity, accompanied by improvements in meaning reconstruction and indicators of personal growth. Several key factors were identified as contributing to this psychological transformation, including an enhanced sense of self, acceptance of reality, expanded cognitive perspectives, the maintenance of continuing bonds with the deceased, and the development of a renewed sense of life purpose. Overall, the results suggest that positive psychology interventions are effective in supporting individuals in coping with prolonged grief and in facilitating the construction of meaningful interpretations of loss and subsequent personal development. Keywords: Prolonged grief; post-traumatic growth; positive psychology; meaning-making.